1976
DOI: 10.1111/j.1476-5381.1976.tb07644.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Relative Effects of Prostaglandins, Bradykinin, 5‐hydroxytryptamine and Histamine on the Synovial Microcirculation in Dogs

Abstract: I The relative effects of prostaglandins E,, E2, Fla, F2a, bradykinin, histamine and 5-hydroxytryptamine (5-HT) on the canine synovial microcirculation were investigated using the rate of clearance ofradioactive xenon ("'Xe) as an index of synovial perfusion.2 All the compounds tested, except prostaglandin F1a, produced a vasodilator effect. The descending order of potency ofthe active compounds was (i) prostaglandin El, (ii) prostaglandin E2 and bradykinin, (iii) histamine and 5-HT, (iv) prostaglandin F2a. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1977
1977
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Chronic inflammation has been associated with elevated levels of PGE2 at the site of injury. PGE2 is a vasodilator (10), enhances vascular permeability (11), and plays a role in the regulation of the immune response by modulating T lymphocyte proliferation, macrophage cytotoxicity, and lymphokine production (12).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic inflammation has been associated with elevated levels of PGE2 at the site of injury. PGE2 is a vasodilator (10), enhances vascular permeability (11), and plays a role in the regulation of the immune response by modulating T lymphocyte proliferation, macrophage cytotoxicity, and lymphokine production (12).…”
Section: Introductionmentioning
confidence: 99%
“…The log of the ratio C,/C0 was plotted against time and the half-life (T1/2 min) of clearance of the gas was obtained by interpolation (or by extrapolation in a few instances). A decrease in T1/2 was taken to denote vasodilatation and an increase to denote vasoconstriction as described by Dick, Grennan & Zeitlin (1976). Each drug, or drug combination, was tested in at least 3 animals.…”
Section: Introductionmentioning
confidence: 99%
“…Prostaglandin E1 has been shown to potentiate the rat paw oedema produced by bradykinin (Moncada, Ferreira & Vane, 1973;Lewis, Nelson & Sugrue, 1975) and to potentiate the actions of bradykinin and histamine in increasing cutaneous vascular permeability in guinea-pigs (Williams & Morley, 1973). No such potentiation was found in our earlier studies on dog synovial blood flow (Dick et al, 1976).…”
Section: Discussionmentioning
confidence: 64%
“…We have previously shown that normal synovial blood flow is extremely sensitive to the vasodilator effects of prostaglandin E1 and bradykinin, and reactive but to a lesser degree, to histamine (Dick, Grennan & Zeitlin, 1976).…”
Section: Introductionmentioning
confidence: 99%